Rice Straws With Different Cell Wall Components Differ on Abilities of Saccharification - Chen, Chen; Deng, Xiaoxiao; Kong, Weilong; Qaseem, Mirza Faisal; Zhao, Shuai; Li, Yangsheng; Wu, Ai-Min (Frontiers in Bioengineering and Biotechnology, 2021)
Rice straw has an enormous amount of biomass for energy use, but the complexity of the cell wall component in different varieties hinders technical processes. Here, 7 different rice varieties (RPY GENG, RIL269, RIL272, RIL31, RIL57, RIL06, LUOHUI 9) with different cell wall traits screened from RIL population were evaluated for their response towards different pretreatments. For japonica RPY GENG, 2% of H2SO4 was best pre-treatment while high acid pretreatment caused undue loss. However, for Indica LUOHUI 9 rice, high acid pretreatment was suitable. RIL57 had a high content of cell wall components, but maximum increase in glucose yield can only be achieved with high alkali pretreatment. High-concentration alkali pretreatment is the most convenient and effective pretreatment method for the treatment of unknown varieties of mixed straw, because the difference in lignin content has the lowest effect on the glucose yield under the condition of 10% NaOH. With the increase of NaOH treatment concentration, RIL31 and RIL269 had the highest (21.2%) and lowest (8.58%) increase in glucose yield, respectively. As the RILs used in this study vary considerably in their wall structure, an understanding of their response to different pre-treatments may help to understand the influence of different wall compositions on the final output.